Biodiesel Production from Rubber Seed Oil Using Activated Cement Clinker as Catalyst - Jolius, Gimbun; Ali, Shahid; Kanwal, Chitra Charan Suri Charan; Liyana, Amer Shah; Nurul Hidayah, Muhamad Ghazali; Cheng, C. K.; Said, N. (Elsevier Ltd, 2013)
This paper presents the potential of limestone based catalyst for transesterification of high free fatty acid (FFA) rubber seed oil (RSO). Pre-calcinated limestone known as clinker was activated using methanol and transesterification was performed under reflux with constant stirring. Mineral composition of the catalyst was analysed using x-ray fluorescence (XRF) with in build x-ray diffraction (XRD). The rubber seed oil was obtained using both microwave and soxhlet extraction using hexane as solvent. FFA content and fatty acid methyl ester content were determined using gas chromatography mass spectrometry (GC-MS). The results showed an efficient conversion (up to 96.9) of high FFA rubber seed oil to biodiesel. The results suggest that the catalyst employed in this work is not negatively affected by moisture and free fatty acids and can be recycled very easily without significant loss in its activity. The highest conversion of 96.9 was achieved from catalyst activated at 700°C, with catalyst loading of 5 wt. ; methanol to oil molar ratio of 4:1; reaction temperature of 65°C and reaction time of 4 hours. The biodiesel produced in this work is within the limits of specification described by American standard test method (ASTM D6751). © 2013 The Authors.